2015
DOI: 10.1111/zph.12238
|View full text |Cite
|
Sign up to set email alerts
|

Intangible and Economic Impacts of Hendra Virus Prevention Strategies

Abstract: Hendra virus (HeV), a potentially fatal zoonotic disease spread by flying foxes, to date has always infected humans via a spillover event from equine HeV infection. In a theoretical case study, we compared the impacts of two different HeV prevention strategies - vaccination and flying fox roost removal - using a recently developed framework that considers different stakeholder group perspectives. The perspectives of the four selected stakeholder groups regarding intangibles were inferred from public discussion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
(36 reference statements)
0
4
0
1
Order By: Relevance
“…As medidas preventivas recomendadas são amplamente divulgadas no local, mas a implementação destas fica a critério dos proprietários de maneira individual (GORDON, 2001;WIETHOELTER et al, 2017). O impacto econômico do HeV é pouco caracterizado, embora o custo médio de suporte e resposta a um surto desta doença esteja estimado em torno de AUD $30.660.00 por cavalo (WILSON; WARD, 2016).…”
Section: Infecção Nos Equinos E Suas Consequênciasunclassified
“…As medidas preventivas recomendadas são amplamente divulgadas no local, mas a implementação destas fica a critério dos proprietários de maneira individual (GORDON, 2001;WIETHOELTER et al, 2017). O impacto econômico do HeV é pouco caracterizado, embora o custo médio de suporte e resposta a um surto desta doença esteja estimado em torno de AUD $30.660.00 por cavalo (WILSON; WARD, 2016).…”
Section: Infecção Nos Equinos E Suas Consequênciasunclassified
“…No therapeutics have been registered for human use but experimental monoclonal antibodies have been used as a compassionate treatment for individuals with high HeV risk exposures [9, 10]. Not including the expense of managing human HeV cases and exposures, the cost and economic loss associated with each localised HeV outbreak has been estimated to be AUD $30,600 for each horse death [11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the introduction and enforcement of protective legislation, current land management strategies for flying-foxes still focus on removing resources to deter the establishment of roosts near human settlements [37]. Experience has shown that relocating flying-fox camps is expensive and almost always fails in the longer term [11, 38]. Rather than solving the problem, dispersal efforts can also lead to the establishment of permanent secondary camps in unexpected and undesirable areas [39].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] There have been 108 horse, and four human deaths from Hendra virus confirmed in Queensland and New South Wales between 1994 and 2022. 10,11 Additionally, with an estimated cost to investigate each potential equine infection of $30,600 12 and ongoing risks to human health, there is a need to better understand the dynamics of this virus and its transmission.…”
mentioning
confidence: 99%